2013
DOI: 10.1123/pes.25.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison in Different Jumping Tasks Between Untrained Boys and Men

Abstract: This study examines the biomechanical differences during different vertical jump tasks in 12 prepubescent and 12 adult males. The sagittal knee kinematics, vertical ground reaction force (vGRF) and electromyographic (EMG) activity of 5 lower extremity muscles were recorded. Compared with boys, men presented higher peak vGRF during the propulsive phase in all examined jumps, but lower values during the braking phase, even when related to body mass. Normalized EMG agonist activity in all phases was higher in men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 43 publications
3
33
4
2
Order By: Relevance
“…Conversely, younger children appear to land with greater knee and hip extension, which combined with heightened muscle co-contraction upon impact, will lead to higher pVGRF (9, 48). Supporting this notion, lower pVGRF related to body mass during the breaking phase of a DVJ have been reported in adults versus boys (25). This may be due to more efficient stretch reflex utilization and greater levels of muscle activation prior to landing and during the breaking phase of the jump (24).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Conversely, younger children appear to land with greater knee and hip extension, which combined with heightened muscle co-contraction upon impact, will lead to higher pVGRF (9, 48). Supporting this notion, lower pVGRF related to body mass during the breaking phase of a DVJ have been reported in adults versus boys (25). This may be due to more efficient stretch reflex utilization and greater levels of muscle activation prior to landing and during the breaking phase of the jump (24).…”
Section: Discussionmentioning
confidence: 66%
“…In order to accurately assess neuromuscular control in male youth soccer players, there is a need for reliable and valid testing protocols (41). Currently in youth males, the most common mode of assessment is measurement of landing forces during a drop vertical jump (DVJ) (24, 25, 40). This protocol has shown strong reliability in male and female high school athletes (ICC range = 0.89 – 0.98) (40).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, O'Brien et al [42] reported higher co-activation levels in adults compared to children, which seems consistent with the greater force production capacity in adults. Finally, higher co-activation levels have been observed in children during poly-articular movements such as walking [53] and jumping [54,55].…”
Section: Antagonist Co-activationmentioning
confidence: 97%
“…It is often related to injuries in basketball, either by stepping on the foot of another player or by any type of imbalance (Mckay, Goldie, Payne, & Cakes, 2001). Several studies have evaluated the landing after the jump (Lazaridis et al, 2013;Nyland et al, 2011;Oliver & Smith, 2010;Ruan & Li, 2010;Un et al, 2013;Ziv & Lidor, 2010) as well as the effect of cooling on electromyographic (EMG) activity and balance oscillation (Fischer, Van Lunen, Branch, & Pirone, 2009), however, the results are still divergent. Schmid, Moffat, and Gutierrez (2010) and Wang, Toner, Lemonda, and Zohar (2010) observed reductions in unipodal vertical jump performance after the use of cryotherapy (with a crushed-ice bag and cold-water immersion, respectively).…”
Section: Introductionmentioning
confidence: 99%